Le rocce scolpite di Dazu - Chongqing, Cina: una valutazione critica dei problemi conservativi di un sito del patrimonio mondiale ed una esperienza personale - Borrelli, Ernesto (Archeomatica, 2015)
Abstract The Dazu Rock Carvings are located in Sichuan province (Chongqing municipality): a sites on the World Heritage List whose majestic rock carvings are of great religious and historical significance. They constitutes one of the most diverse forms of cultural heritage particularly present in China as the Yungang Grottoes , the rock carvings of Longmen and all represent one of the most demanding challenges for their conservation. This paper offer a critical appraisal of the conservation problems of the site, it would be a review on the past and current action to preserve the site, on the scientific research, and on the environmental and geotechnical aspects of conservation. The main feature of this article is scientific, but it is rather the story of a professional fascinating experience of a Western observer and conservationist approaching the Chinese cultural heritage. The paper includes an updated survey of the literature including an unusual use of repeated citations of a nice old book "The Chinese diary" of the Italian art historian Cesare Brandi, worldwide known as the author of the "Theory of Restoration” and founder (1939) of the Italian Institute for Conservation and Restoration of Cultural Heritage.